Development of Buoy-based Observation Module (B.O.M.) for Headwater Monitoring and Early Warning System - Othman, Muhammad Azwar Hakim; Abdul Kadir, Herdawatie (Evolution in Electrical and Electronic Engineering, 2025)
Recreation areas and waterfalls are often visited to experience the peace of nature. In recreational areas and waterfalls, headwater disasters can occur; this disaster often worries visitors and residents. This study aims to reduce human casualties and help mitigate the public by developing an early warning system, namely the Buoy-based Observation Module (B.O.M.). Evacuation and emergency planning activities get underway faster with a trustworthy early warning system. Therefore, developing technologies like this can help monitor and provide early warning signs based on LoRa and IoT technologies. This system aims to improve the preparedness of recreational area controllers to face disasters in recreational areas. This module is designed to monitor environmental changes such as vibration, rain, temperature, humidity, and orientation, such as significant changes in angle to the installed module. With various sensors, it allows the system to provide early warning of potential water disasters. Among the additional technologies that have been improved from previous technologies are LoRa and IoT communication technology. It is used to ensure efficient and fast data transmission in real time. Construction of the B.O.M. was structured to withstand heavy rain. By being equipped with solar panels, the B.O.M module can ensure sufficient energy, and there is backup energy. Findings from this study also evaluate aspects such as function, performance, visualization, data communication, and the warning system. At the end of the study, it was found that this system showed that it works well in various environmental conditions and is effective in early warning of disasters in watershed areas.